PENGEMBANGAN PERANGKAT PEMBELAJARAN INSTALASI LISTRIK TENAGA SURYA UNTUK RUMAH PINTAR DENGAN MODEL PEMBELAJARAN PROJECT BASED LEARNING - Setiarto, Budi; Ekohariad, Ekohariad; Suprianto, Bambang (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
ABSTRACT This research is conducted since the electric technique teachers in East Kalimantan are demanded to prepare the competent graduation in the solar electric installation. The learning set which is developed in this research is completed by smart solar home system kit. That is a learning tool in the form of home miniature by using PIR censor as the automatic door service, light censor by using LDR as the automatic lamp service and temperature censor by using NTC as the air conditioning service to make the learning process by using Project Based Learning runs well. This research is conducted in to steps, it is started by developing the learning set and it is continued by experimental step by using nonequivalent control grup design. This research aims to find the feasibility of the learning set which is developed and to find the difference of study result between the students who use the solar electric installation learning set by using direct learning. The data collecting technique used are observation, validation and tes.The researcher uses analysis of covariance by using statistic data software to analyze the hypothesis, t. The result of the research shows that the learning set is valid to be implemented. It consist of: (a) the syllabus is valid and gets a very good category, (b) the lesson plan is very good category, (c) the students? worksheet is valid and gets a good category, (d) scoring sheet is valid, (e) the students? book is valid and gets a good category, (f) the learning kits is valid and gets a good category. Furthermore, based on the results of statistical analysis used in the study, it was found that (F: 0220; p> 0.05) and (. Sig .641). it can be concluded that there is a difference in learning outcomes between students in the class controlled using direct learning and students in classroom experiments using model project based learning after they were given treatment, but the difference was not significant Keywords: Developing Learning Set, Project Based Learning, Solar Electric Installation for Smart Home